Workstation Capacity Optimization Using Theory Of Contraint and Drum-Buffer-Robe Methods - mutia meilanda; Rr. Rochmoeljati (Electronic Journal of Education, Social Economics and Technology, 2026)
A company in Pasuruan that produces speaker components is facing a bottleneck problem in cone paper production due to fluctuations in demand resulting in an imbalance in machine capacity and cycle time. This results in the cone paper production process being inefficient in meeting targets, making throughput suboptimal. To overcome these problems, you can apply Theory of Constraints (TOC) through the Drum-Buffer-Rope approach and Linear a Programming which is processed using WinQSB software. The research phase includes constraint identification, constraint exploitation, constraint subordination and constraint elevation. Based on the calculation, botlleneck occurs at the cone printing (SK -1) and coating (SK - 4) work stations. To overcome this, 2 hours of overtime was added at both work stations in August 2024 - January 2025. This step successfully increased throughput, the initial throughput of 80,669,0700 increased by 99,103,4200 or 19%. Thus, this proposal proved to be effective in optimizing throughput and maximizing production capacity utilization.